“Throw in the towel!”: reality of executives women that decide to return home. Discussion about opt-out phenomenon - Reis, Sally Joice (2021)
The present study aims at understanding the reasons thatled some executives to give up their careers and choose toreturn home. It is a qualitative study through the life history´smethodology. The data collection took place from an in-depthinterview using as subjects two executives women. The research brings to a reflection about this position of abandonment,since, historically, there is a division between the sexes, aspectthat allows to understand why women finds many challengeswith respect to the ascension and the maintenance of its race inthe corporate world. The great contribution of this study was toadvance in the reasons that result in the opt-out phenomenon,little explored in the literature.